Learning by lectures in a transnational university in China: Integration and resistance during the transition from high school to university - Miani, Mattia (Journal of International Students, 2026)
This multiyear study investigates how first-year undergraduates make sense of large content lectures during their transition from domestic high schools to a transnational university in China. Grounded in a view of learning and teaching practices as interactional accomplishments, the data collection included lecture observations, focus groups, and interviews with 34 students across three academic years, as well as an additional interview with departmental leadership. A qualitative content analysis revealed how students positioned lectures as knowledge hubs, spaces for sociality, and objects of resistance. While many students valued lectures for their informative qualities and opportunities for socialization, others actively resisted lectures by leveraging the affordances of technology when they perceived lectures as not contributing to their learning. These patterns are interpreted through the lens of the glocal nature of a transnational site and the interactional nature of lectures, where teachers’ and students’ practices intersect. The study contributes to scholarship on lecturing and student transition by highlighting the diversity of student experiences in large content lectures and reframing engagement as an alignment between students’ and teachers’ practices. The study yields practical recommendations for critically rethinking lectures at a transnational site to ensure alignment among all parties involved.